Obstructed or Malpositioned Urethral Catheter Induced Acute Kidney Injury - Ankita Patel; Eli A. Friedman (Case Reports in Nephrology)
Unanticipated renal failure may be induced by an obstructed urethral catheter that was a component of complex management or difficult insertion. Two patients with new-onset uremia due to obstructed urethral catheters evinced rapid return of renal function when their blocked catheters were replaced.